Capital budgeting practice in India : a case study of ACC - Gupta, Ashish; Pandey, Indra M.; Gupta, Joyti; Swierczek, F.W.; Asian Institute of Technology Partial (Bangkok : Asian Institute of Technology, 1996)
This study was carried out to study how Capital Budgeting is done in a big Indian company. First, industry analysis is done to understand the business environment of the company. Then, it was studied, how the competitive environment is affecting the company's business. Finally, an actual case of the company's investment is taken for better understanding of the capital budgeting practice in the company. The data collection was done on the basis of interviews of various executives of the company. It was found that the investment process in the company is satisfactory but company's method of calculating cost of equity is not appropriate. Due to inappropriate method of calculating cost of equity company might be rejecting some good investment opportunities. Also, there are no incentives for initiating a new investment proposal and company doesn't do any post audit. There is a need to improve the investment process in the company.
A research study submitted in partial fulfilment of the requirements for the degree of Master of Business Administration.
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 1996
Keywords: Capital budget